Invasiveness does not predict impact: response of native land snail communities to plant invasions in riparian habitats - Horáčková, Jitka; Juřičková, Lucie; Šizling, Arnošt L; Jarošík, Vojtěch; Pyšek, Petr (PloS one, 2014)
Studies of plant invasions rarely address impacts on molluscs. By comparing pairs of invaded and corresponding uninvaded plots in 96 sites in floodplain forests, we examined effects of four invasive alien plants (Impatiens glandulifera, Fallopia japonica, F. sachalinensis, and F.× bohemica) in the Czech Republic on communities of land snails. The richness and abundance of living land snail species were recorded separately for all species, rare species listed on the national Red List, and small species with shell size below 5 mm. The significant impacts ranged from 16-48% reduction in snail species numbers, and 29-90% reduction in abundance. Small species were especially prone to reduction in species richness by all four invasive plant taxa. Rare snails were also negatively impacted by all plant invaders, both in terms of species richness or abundance. Overall, the impacts on snails were invader-specific, differing among plant taxa. The strong effect of I. glandulifera could be related to the post-invasion decrease in abundance of tall nitrophilous native plant species that are a nutrient-rich food source for snails in riparian habitats. Fallopia sachalinensis had the strongest negative impact of the three knotweeds, which reflects differences in their canopy structure, microhabitat humidity and litter decomposition. The ranking of Fallopia taxa according to the strength of impacts on snail communities differs from ranking by their invasiveness, known from previous studies. This indicates that invasiveness does not simply translate to impacts of invasion and needs to be borne in mind by conservation and management authorities.
Keywords: Biodiversity; Snails; Population Dynamics; potravní řetězec; biodiverzita; zavlečené druhy; Introduced Species; Animals; populační dynamika; hlemýždi; zvířata; hustota populace; Population Density; Food Chain